Leaf Morphology of Brazilian Spinach (Alternanthera sissoo) as a Backyard Vegetable - Hikma Ellya; Nurlaila Nurlaila; Nukhak Nufita sari; Rila Rahma Apriani; Ronny Mulyawan; Bakti nur Ismuhajaroh (International Journal of Agricultural Sciences, 2021)
The utilization of backyard gardens to fulfill family food by the Indonesian people needs to be developed, along with fulfilling nutrition during the Covid-19 pandemic. One of the plants that have the potential to grow is Brazilian spinach (Alternanthera sissoo). References on the morphology of Brazilian spinach are still limited, so it is necessary to observe the plant organs. This study aims to determine the leaf morphology of Brazilian spinach as vegetables in backyard gardens. Morphological observations of these spinach leaves were carried out visually at the Integrated Laboratory of the Agroecotechnology Department, Faculty of Agriculture, Lambung Mangkurat University, in August 2020. The results showed that Brazilian spinach has a herbaceous with a simple leaf in a deltoid shape (deltoideus). It has tapered leaf tips (acuminatus); acuminated leaf base (acuminatus); wavy leaf margin (repandus); and simple palmate leaf venation (palminervis). The arrangement of its leaves is folia decussate, where each nod has two leaves that emerge opposite each other